(untitled) (International Journal of Engineering and Computer Science, 2014)
Mobile systems have limited resources, such as battery life, storage capacity, and processor performance. These restrictions overcome by computation offloading. Energy efficiency is a fundamental consideration for mobile devices. Mobile Cloud Computing (MCC) is a model for flexible growth of mobile device capabilities via universal wireless access to cloud storage and computing resources. Rather than conducting all computational and data operations locally, MCC takes advantage of the abundant resources in clouds to store and process data for mobile devices. Our objective is to conserve energy for the mobile device, by optimally executing mobile applications in the mobile device (i.e., mobile execution) or offloading to the cloud (i.e., cloud execution). Our framework for energy optimal execution of applications derived a condition when offloading is beneficial and amount of energy saved by optimal execution of application. Proposed system demonstrated significant gain in execution speed and battery life of mobile phones.